Factor V Leiden and Fatal Pulmonary Embolism - Vandenbroucke, Jan P.; Bertina, Rogier M.; Holmes, Zandra M.; Spaargaren, Caroline; van Krieken, Joannes H. J. M.; Manten, Bert; Reitsma, Pieter H. (Thrombosis and Haemostasis, 1998)
To investigate whether the factor V Leiden mutation increases the risk of fatal pulmonary emboli, we determined the presence of the factor V Leiden mutation in pathology material from two series of autopsies of patients from the Leiden University Hospital, The Netherlands. The first series consisted of consecutive autopsies in which pulmonary emboli were mentioned in the autopsy report; most patients of this series had major underlying disease. The second series consisted of autopsies in patients younger than age 70 in which pulmonary emboli were the sole cause of death and no major acquired risk factor for venous thrombosis was present. Extraction of DNA was done on newly prepared tissue from archival paraffin blocks. In the first series, the presence of factor V Leiden was determined in 44 patients, 1 of whom carried the mutation (2.3 percent; 95% confidence interval 0.06 to 12.0 percent). This prevalence is not different from the general population prevalence in The Netherlands. In the second series, factor V Leiden could be determined in 30 patients of whom 3 carried the mutation (10 percent; 95% confidence interval 2.1 to 26.5 percent), which would lead to a threefold relative risk. A large number of patients with diverse psychiatric diagnoses was present in the second series (eleven). We conclude that in the presence of severe illness, the factor V Leiden mutation plays no additional role in the development of pulmonary emboli. The relative risk of the very rare fatal pulmonary embolus that is the sole cause of death might also be less than the relative risk for deep-vein thrombosis in carriers of the factor V Leiden mutation.